2006
DOI: 10.1210/jc.2006-0305
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mutant UDP-N-Acetyl-α-d-Galactosamine-Polypeptide N-Acetylgalactosaminyltransferase 3 in Regulating Serum Intact Fibroblast Growth Factor 23 and Matrix Extracellular Phosphoglycoprotein in Heritable Tumoral Calcinosis

Abstract: Our findings demonstrate that GALNT3 inactivation in patients with TC leads to inadequate production of biologically active FGF23 as the most likely cause of the hyperphosphatemic phenotype. Furthermore, combination therapy may be effective for reducing the tumoral burden associated with familial TC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 24 publications
3
76
2
1
Order By: Relevance
“…The Thr 171 site is also glycosylated by several other ppGalNAc-T isoforms (21). Our previous work (43) utilizing transferase specific preferences, obtained from random peptide studies, also suggests that Thr 171 would be a moderate to good substrate for ppGalNAc T1, T2, and T3, whereas Thr 178 would not be a substrate for ppGalNAc T1 or T2 and would be only a modest substrate for ppGalNAc T3 (see Table 2 , whose glycosylation is required to inhibit the proprotein convertase cleavage of FGF23 in vivo and in vitro (20,21,74).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The Thr 171 site is also glycosylated by several other ppGalNAc-T isoforms (21). Our previous work (43) utilizing transferase specific preferences, obtained from random peptide studies, also suggests that Thr 171 would be a moderate to good substrate for ppGalNAc T1, T2, and T3, whereas Thr 178 would not be a substrate for ppGalNAc T1 or T2 and would be only a modest substrate for ppGalNAc T3 (see Table 2 , whose glycosylation is required to inhibit the proprotein convertase cleavage of FGF23 in vivo and in vitro (20,21,74).…”
Section: Discussionmentioning
confidence: 96%
“…8 Likewise, studies on the glycan binding requirements of the lectin domain of ppGalNAc T3 suggest that this transferase utilizes its lectin domain to glycosylate residues C-terminal of the site of prior glycosylation (55), again in keeping with our findings for ppGalNAc T3. ppGalNAc T3 was previously shown to be the only isoform capable of glycosylating the proprotein processing region of FGF23 (IHFNT 171 PIPR RHT 178 R2SAEDD) (21,25,74), and in unpublished work, 9 Kato et al have found that ppGalNAc T3 glycosylates the Thr 178 site in a lectin-dependent manner by first glycosylating Thr 171 in a lectin-independent manner, both in in vitro enzyme assays and ex vivo in CHO cells stably transfected with ppGalNAc T3 variants. The Thr 171 site is also glycosylated by several other ppGalNAc-T isoforms (21).…”
Section: Discussionmentioning
confidence: 97%
“…This gene encodes a protein called UDP-N-acetyl-a-D-galactosamine: polypeptide N-acetylgalactosaminyltransferase-3 (ppGaNTase-T3) and is involved in post-translational modifications of serine or threonine residues by O-glycation; patients with FTC that (Garringer et al 2006). Circulatory FGF23 levels are also extremely high in patients with CKD , Imanishi et al 2004.…”
Section: Fgf23mentioning
confidence: 99%
“…[9][10][11][12][13][14] Indeed, the importance of the interactions between these factors is highlighted by the findings that loss of function mutations in aKL 15 and FGF23 [16][17][18][19] lead to the Mendelian disorder hyperphosphatemic familial tumoral calcinosis. In the reciprocal setting, gain of function mutations in FGF23 result in increased blood FGF23 and autosomal dominant hypophosphatemic rickets.…”
mentioning
confidence: 99%